Noise‐based seismic monitoring of the Campi Flegrei caldera. Issue 5 (15th March 2017) - Zaccarelli, Lucia; Bianco, Francesca
Abstract: The Campi Flegrei caldera is one of the highest risk volcanic fields worldwide, because of its eruptive history and the large population hosted within the caldera. It experiences bradiseismic crises: sudden uplift with low energetic seismic swarm occurrences. No seismicity is recorded out of these deformation rate changes. Therefore, a continuous seismic monitoring of the caldera is possible only by means of the ambient seismic noise. We apply a noise‐based seismic monitoring technique to the cross correlations of 5 year recordings at the mobile seismic network. The resulting relative velocity variations are compared to the temporal behavior of the geophysical and geochemical observations routinely sampled at Campi Flegrei. We discriminate between two kinds of crustal stress field variations acting at different timescales. They are related to a possible magmatic intrusion and to the gradual heating of the hydrothermal system, respectively. This study sets up the basis for future volcano monitoring strategies. Key Points: Noise‐based seismic monitoring applied to 5 year continuous recordings of the Campi Flegrei seismic network Comparison between time series of all geophysical and geochemical observations Interpretation of unrest phases at Campi Flegrei caldera